Knowledge banks: using technology to enhance vocabulary development - Guy, Denise M. (Kansas State University, 2006)
As students are required to learn more and more and the world of technology evolves with access to information, how can schools use this knowledge to help students learn? This project focuses on the development of a prototype tool to assist students in building a vocabulary over time. The tool will allow students to capture definitions using research based graphic organizers. It also has a variety of ways students can represent the new words non-linguistically – graphically, audio, adding a variety of files. A prototype of this tool was developed and expert teachers reviewed the tool for functionality. Students were also asked to review the tool. After revisions were made students were asked to use the tool in class in a preliminary field test. Students were then asked their opinion on how they felt this tool would help them learn. This study involved four students and their experiences using the Knowledge Banks. The students overwhelmingly felt the tool would help them to organize their information, give them easier access to finding the information at a later date, and allow them ways to represent the new information non-linguistically. They enjoyed the ability to search for terms and find all the information that was connected to this term in any way. Having all of this information allowed them to make connections with their information they hadn’t done before. The implications of this study on education include; the need to provide ways for students to collect and build their knowledge, giving them access to tools for storage, allowing them to search their knowledge therefore making connections to new learning. This study showed that a tool can be developed that will help students learn new vocabulary and allow students to continue to learn this vocabulary by revisiting the terms over and over again year after year.
Keywords: Knowledge; Vocabulary; Technology; Education, Curriculum and Instruction (0727)